The Antagonistic Activity of Bioactive Compound Producing Streptomyces of Fusarium Wilt Disease and Sheath Blight Disease in Rice - Mathurot Chaiharn (Science Faculty of Chiang Mai University, 2019)
Rhizospheric actinomycetes were screened for bioactive compound production such as antibiotic, siderophore and cell wall degrading enzyme against Fusarium wilt disease and sheath blight disease in rice which are caused by Fusarium oxysporum and Rhizoctonia solani AG-2, respectively. A total of 150 strains was classified based on their cultural and physiological characterization such as color of aerial mycelium, color of substrate mycelium and spore chain morphology combined with cell wall composition analysis. They were classified as Streptomyces (52.7 %), non-Streptomyces (35.3 %) and unidentified (12 %). Involvement of cell wall degrading enzymes such as chitinase, cellulase and β-1,3-glucanase was investigated. Results showed that isolate RHI-43 produced high levels of chitinase (3.50 U/ml), cellulase (4.90 U/ml) and β-1,3-glucanase (0.45 U/ml) while isolate RHI-114 produced high levels of protease (15 U/ml). On the basis of dual culture assays, isolate RHI-39 and isolate RHI-146 were selected on the basis of broad spectrum activities and identified using cell wall composition analysis combined with 16S rDNA analysis and phylogenic classification. These isolates were identified as Streptomyces lydicus (for isolate RHI-39) and Streptomyces corchorussi (for isolate RHI-146). Further, culture filtrates of isolate RHI-146 inhibited the growth of all fungi tested which showed hyphal swelling and abnormal shapes of tested fungi under microscope. These results suggest that Streptomyces isolate RHI-39 and Streptomyces isolate RHI-146 may be utilized as an environmental friendly biocontrol agent against some important rice-pathogenic fungi in vitro.